PENGARUH SISTEM INFORMASI AKUNTANSI (SIA) TERHADAP KEBERLANGSUNGAN UMKM BALI - Braven Abhiel Sariwating; Made Trisna Adhi Dwipayani; Made Nadia Savita Putri Pramana; Nurul Aisyah; Rafael Valentino Indrawan; Shakyla Sifa Sofiani; Jovi Muhammad; Ni Putu Trisna Nadia (PT. Saha Kreasi Indonesia, 2025)
Bali is known for its prominent tourism sector. However, Bali's MSMEs still face several shortcomings compared to the tourism sector. One of the challenges faced by MSMEs in Bali is inadequate financial reporting methods. Therefore, the gradual implementation of an Accounting Information System (AIS) can improve the efficiency of financial management in Bali's MSMEs. An AIS enables automated transaction recording, real-time data analysis, and integration with digital platforms such as cloud computing, thereby minimizing human error and accelerating decision-making. This study aims to examine the development of MSMEs that do and do not implement AIS in financial data management.